Treatment results and prognostic factors in primary thyroid lymphoma patients: a Rare Cancer Network study - ATASOY, BESTE MELEK (OXFORD UNIV PRESS, 2011)
Background: This study analyzed prognostic factors and treatment outcomes of primary thyroid lymphoma. Patients and Methods: Data were retrospectively collected for 87 patients (53 stage I and 34 stage II) with median age 65 years. Fifty-two patients were treated with single modality (31 with chemotherapy alone and 21 with radiotherapy alone) and 35 with combined modality treatment. Median follow-up was 51 months. Results: Sixty patients had aggressive lymphoma and 27 had indolent lymphoma. The 5- and 10-year overall survival (OS) rates were 74% and 71%, respectively, and the disease-free survival (DFS) rates were 68% and 64%. Univariate analysis revealed that age, tumor size, stage, lymph node involvement, B symptoms, and treatment modality were prognostic factors for OS, DFS, and local control (LC). Patients with thyroiditis had significantly better LC rates. In multivariate analysis, OS was influenced by age, B symptoms, lymph node involvement, and tumor size, whereas DFS and LC were influenced by B symptoms and tumor size. Compared with single modality treatment, patients treated with combined modality had better 5-year OS, DFS, and LC. Conclusions: Combined modality leads to an excellent prognosis for patients with aggressive lymphoma but does not improve OS and LC in patients with indolent lymphoma.
Keywords: chemotherapy; combined modality treatment; non-Hodgkin's lymphoma; prognostic factors; radiotherapy; thyroid lymphoma; B-CELL LYMPHOMA; NON-HODGKINS-LYMPHOMA; MALIGNANT-LYMPHOMA; LOCALIZED INTERMEDIATE; ONCOLOGY-GROUP; GLAND; RADIOTHERAPY; CHEMOTHERAPY; THERAPY; CHOP